1994
DOI: 10.1520/jfs13611j
|View full text |Cite
|
Sign up to set email alerts
|

Firearm Suicides During Confrontations with Police

Abstract: We reviewed the case records of suicides in Marion County, Indiana (Indianapolis) and in surrounding counties from 1984 through 1992. Out of 1203 suicides, there were 14 in which armed, on-duty police officers were confronting, pursuing, or apprehending the subject of the death investigation. All subjects were male, and the peak age range was 30 to 34 years. The head, especially the right temple, was the usual site of the fatal wound. More than half of the incidents started as domestic disputes with a wife or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
0
9
1
Order By: Relevance
“…Use of poisons, self-immolation, hanging, drowning and sometimes use of firearms account for most of the suicides in this part of the world. This is in contrast to various studies reported from time to time from other countries (Avis, 1994;Harruff, 1994;Bullock, 2000;Campman, 2000;Gupta, 2000;Marc, 2000;Siciliano, 2000). The present study reveals that males preferred poisoning and hanging whereas females showed a preference for fire (burns) in contrast to a study that reported male predominance in cases of selfimmolation (Cooper, 1994).…”
Section: 05contrasting
confidence: 99%
“…Use of poisons, self-immolation, hanging, drowning and sometimes use of firearms account for most of the suicides in this part of the world. This is in contrast to various studies reported from time to time from other countries (Avis, 1994;Harruff, 1994;Bullock, 2000;Campman, 2000;Gupta, 2000;Marc, 2000;Siciliano, 2000). The present study reveals that males preferred poisoning and hanging whereas females showed a preference for fire (burns) in contrast to a study that reported male predominance in cases of selfimmolation (Cooper, 1994).…”
Section: 05contrasting
confidence: 99%
“…The use of deadly force by law enforcement often entails the public interactions of the police, district attorneys, social activists, the media, elected government officials, families of the victims, and the medical examiner/coroner (1–5). The forensic pathologist who investigates, performs the autopsy, and certifies these deaths often is scrutinized and second guessed.…”
mentioning
confidence: 99%
“…If the robber, in desperation, tries to ''shoot his way out,'' his death should not be certified a suicide unless it could be shown that prior to the attempted robbery, the decedent was intending to end his life through this confrontation with the police. If, however, that robber shoots himself in this inescapable situation (so-called police-associated death), then a suicidal manner is appropriate (17). ME ⁄ C who certify these ''suicide by cop'' deaths as suicides are at risk of being accused of a cover-up for the police.…”
Section: Discussionmentioning
confidence: 99%